Effect of hygiene of kitchen utensils and food handlers on microbial counts in Jumbo Ayahanda Iced Tea drinks, Medan City - Manalu, Madeline Elisa Patricia; Waruwu, Fransiska Lalania; Siagian, Masryna; Hulu, Victor Trismanjaya; Pakpahan, Eka Lolita Eliyanti (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Food safety is a crucial aspect of public health, aiming to prevent diseases resulting from the consumption of contaminated food or beverages. This study employed a quantitative research design with an analytical observational approach. The analytical observational method was used to determine the relationship between two independent variables—kitchen utensils and food handler hygiene—and the dependent variable, the microbial count in jumbo iced tea beverages sold along Ayahanda Street, Medan. The quantitative approach was chosen for its ability to measure data numerically and statistically analyze the relationships among variables. Data collection was conducted through direct observation using standardized assessment sheets. The kitchen utensil variable included evaluation of the cleanliness of plastic cups, straws, cool boxes, and cup sealer machines; washing procedures; equipment storage; cleaning methods for stainless steel, glass, and food-grade plastic tools; as well as cleaning frequency. The food handler hygiene variable was assessed based on hand hygiene before and after beverage preparation, nail cleanliness, cleanliness of clothing and aprons during work, and the use of personal protective equipment such as masks and gloves. Microbiological testing involved determining the Total Plate Count (TPC) and comparing the results with established safety standards. Observational and laboratory data were processed and analyzed statistically using the Chi-Square test with a 5% significance level (α = 0.05) to evaluate the effect of kitchen utensil conditions and food handler hygiene on microbial counts. The results showed that the majority of jumbo iced tea samples contained microbial levels within safe limits. Of the 30 samples tested, only 4 samples (13.3%) contained detectable microbes, while 26 samples (86.7%) showed no microbial growth based on the Total Plate Count method. There was no significant association between kitchen utensil cleanliness and microbial counts in jumbo iced tea sold on Ayahanda Street, Medan (p-value = 0.507). However, a significant relationship was found between food handler hygiene and microbial counts in the same products (p-value = 0.024).